Effect of Gear Transmission System to Vibration Test Machine - Abdul Khair Junaidi; Weriono Weriono; Nazaruddin Nazaruddin; Deden MS (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2023)
This research aims to investigate the vibration analysis for equipment test of chassis. The frame model of the gear transmission vibration test is developed. The prototype of the vibration and noise testing tool was constructed for the gear transmission system. The vibration equipment test consists of three gears that function as a gear transmission. The chassis is considered to be one of the vital elements of equipment. The rotation of gears and shafts can occur the vibration. The simulation with the 3D model using ANSYS was resulted in structure analysis. The simulation was resulted in total deformation, equivalent strain, and equivalent stress where the structure of the equipment was definitely safe and had good stability.